Disguising Exploitation. Immigrants in the Ecuadorian Gig Economy - María Belén Albornoz; Henry Chavez (Trilogía Ciencia Tecnología Sociedad, 2023)
Ecuador is home to approximately 556,000 immigrants, mostly from Venezuela (65%) and Colombia (25%), many of whom have an irregular immigration status. In Ecuador, an immigrant without a visa cannot work, which creates a scenario that favours abuse by employers and hinders immigrants’ ability to organize and negotiate their rights. Part of this population has found the platform economy to be a flexible way to find work and earn an income quickly. However, this has also given rise to new forms of exploitation. The objective of this article is to analyse the relationship between the development of the platform economy in Ecuador and the labour conditions of the migrant population that has entered the country in recent years. We used a qualitative methodology based on direct observation, semi-structured interviews (46) and in-depth interviews (10). The main results of this research show that the development of the platform economy and the lack of adequate legislation have produced new forms of disguised exploitation, particularly of immigrant workers. These new forms of exploitation operate through a black market of profile and vehicle subcontracting which, in their interaction with the algorithmic management systems of these applications, end up worsening the already precarious working conditions of the migrant population that uses these applications as a means of survival. The article concludes with a brief analysis of these working conditions in relation to the five principles of fair work.